1995
DOI: 10.1037/0022-0663.87.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, interest, and narrative writing.

Abstract: One-hundred-six 9th graders and 203 undergraduates wrote a story about baseball for 25 min and then completed a 39-item multiple-choice test of baseball topic knowledge. Students also answered 6 questions about their individual interest in baseball. Confirmatory factor analysis suggested that knowledge and interest tests measured different constructs. Hierarchical regression analyses revealed Grade X Interest and Gender X Interest interactions on thematic maturity. Differences favoring undergraduates at low le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 35 publications
2
40
0
Order By: Relevance
“…Domain knowledge, on the other hand, resulted in differences in the degree to which writers incorporated game-relevant propositions into the narrative accounts of a half-inning of baseball (Benton et al, 1995;Voss et al, 1980). A growing body of evidence suggests that both reading and writing skills are dependent on both verbal ability and domain-specific knowledge (Adams, Bell, & Perfetti, 1995;Benton et al, 1995;McCutchen, 1986;Singer & Ritchot, 1996). Kintsch's (1988) construction-integration model has been chiefly applied to reading, but it is also relevant to text production (Nicolich, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Domain knowledge, on the other hand, resulted in differences in the degree to which writers incorporated game-relevant propositions into the narrative accounts of a half-inning of baseball (Benton et al, 1995;Voss et al, 1980). A growing body of evidence suggests that both reading and writing skills are dependent on both verbal ability and domain-specific knowledge (Adams, Bell, & Perfetti, 1995;Benton et al, 1995;McCutchen, 1986;Singer & Ritchot, 1996). Kintsch's (1988) construction-integration model has been chiefly applied to reading, but it is also relevant to text production (Nicolich, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Participants wrote a narrative account of a half-inning of a baseball game. The propositions expressed were categorized according to whether they were game actions, relevant-nongameactions, or irrelevant-nongame actions, as in previous work (Benton et al, 1995;Voss et al, 1980). It was anticipated that a high degree of domain knowledge would increase the proportion of game-relevant actions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies show that topical interest has a stronger effect on the application and transfer of knowledge and on engagement towards the topic rather than on simple activities like recognition of facts [69]. Benton et al [8] found that individuals who were interested in the topic wrote better quality essays, both in terms of relevant information included and the thematic complexity of the sentences. Tobias and Everson [76] discovered that interest in the topic was positively related to metacognition (the ability to understand and monitor one's cognitive processes).…”
Section: Defines Motivations As "A Set Of Energetic Forces That Origimentioning
confidence: 99%